Relatório do estágio curricular supervisionado em medicina veterinária - área de clínica médica e cirúrgica de pequenos animais - Primaz, Sandy Liara (2015)
The activities monitored and \ or developed as a result of the Supervised Curricular Internship in Veterinary Medicine (ECSMV) are described in this report. The Veterinary Hospital of Small Animals (HVPA) of the Federal Rural University of Rio de Janeiro (UFRRJ), located in the city of Seropédica, RJ, was chosen as an internship location. Professor Paulo Souza Junior supervised and supervised the Veterinary Doctor, assistant professor Jonimar Pereira Paiva. It covered the areas of medical clinic and small animal surgery. The internship was developed in 8 hours daily, resulting in a total practical workload of 480 hours. The same occurred in the period from August 3 to October 30, 2015.